Analisis Wacana Politik Peluang Kalimantan Tengah dalam Pembangunan Ibu Kota Nusantara pada Debat Publik Calon Gubernur dan Wakil Gubernur Kalimantan Tengah Tahun 2024 - Ul'zikri, Ahmad Robi; Annisa, Syifa Nur (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2024)
This research analyzes Central Kalimantan’s opportunities in developing the Indonesian Capital City (IKN) through the discourse that emerged in the public debate of candidates for governor and deputy governor of Central Kalimantan in 2024. Using a critical discourse analysis approach, data in the form of debate transcripts were analyzed using NVivo 15 software to identify key themes, discourse patterns, and relationships between issues. The research results show that there are six political discourses in the debate, namely: infrastructure development, natural resource management, and human resource empowerment are the main themes in the debate. The couple Abdul Razak and Sri Suswanto and the couple Agustiar Sabran and Edy Pratowo both have percentage coverage highest on the issue of job creation (34.53%), Nadalsyah and Supian Hadi highest on the issue of opportunities for Central Kalimantan as a buffer for IKN food security (11.85%). Meanwhile Willy M Yosef and Habib Said have percentage coverage highest on the issue of infrastructure development opportunities. This research contributes to the development of strategic policy through political discourse for regional head candidates who will be elected in translating the position and reading of Central Kalimantan’s opportunities as a buffer for the capital of the archipelago on its policy priority scale.